Infantile spasms in down syndrome: Rescue by knockdown of the GIRK2 channel. Issue 4 (13th August 2016) - Joshi, Krutika; Shen, Lily; Michaeli, Avner; Salter, Michael; Thibault‐Messier, Gabrielle; Hashmi, Sumaiya; Eubanks, James H.; Cortez, Miguel A.; Snead, O. Carter
Abstract : Objective: The Ts65Dn (Ts) mouse model of Down syndrome (DS) is exquisitely sensitive to an infantile spasms phenotype induced by γ‐aminobutyric acidB receptor (GABAB R) agonists. The Ts mouse contains the core genomic triplication of the DS critical region, which includes 3 copies of the Kcnj6 gene that encodes the GABAB R‐coupled G protein‐coupled inward rectifying potassium channel subunit 2 (GIRK2) channel. We test the hypothesis that GIRK2 is necessary for the GABAB R agonist‐induced infantile spasms phenotype in Ts. Methods: We assessed the result of either genetic or pharmacological knockdown of the GIRK2 channel in Ts brain upon the GABAB R agonist‐induced infantile spasms phenotype in the Ts mouse model of DS. As well, we examined GABAB R currents in hippocampal neurons prepared from GIRK2‐trisomic Ts control mice and GIRK2‐disomic Ts mice in which Kcnj6 had been genetically knocked down from 3 to 2 copies. Results: The reduction of the copy number of Kcnj6 in Ts mice rescued the GABAB R agonist‐induced infantile spasms phenotype. There was an increase in GABAB R‐mediated GIRK2 currents in GIRK2‐trisomic Ts mouse hippocampal neurons, which were normalized in the GIRK2‐disomic Ts mice. Similarly, pharmacological knockdown of the GIRK2 channel in Ts brain using the GIRK antagonist tertiapin‐Q also rescued the GABAB R agonist‐induced infantile spasms phenotype in Ts mutants. Interpretation: The GABAB R‐coupled GIRK2 channel is necessary for the GABAB R agonist‐induced infantile spasms phenotype in the Ts mouse and may represent a novel therapeutic target for the treatment of infantile spasms in DS. Ann Neurol 2016;80:511–521